Sistem Informasi Usaha Mikro Kecil dan Menengah (UMKM) Kabupaten Lamongan - Sufaidah, Siti; Fauzi, Hermawan Setyo (Exact Papers in Compilation (EPiC), 2022)
Lamongan Regency is one of the regencies in East Java that is developing the MSME program with a total of 130,006 business actors and is able to absorb a workforce of 327,422 people and is able to score an increase in East Java's GDP of 66.59%. The data shows that MSMEs in Lamongan have the potential to be developed. The observation results show that there are still many MSME actors who market their products traditionally. This is very unfortunate because almost all MSME actors have technological tools such as smartphones which should be used as marketing media. The purpose of this research is to simplify and increase the market reach of MSME actors in marketing their products through the development of a web-base equipped with voice features and Google maps. The research was conducted from March to May 2022. The method used in this research is an experimental method with a quantitative approach. The system development model used is the waterfall method. The results of the study show that the developed web-base is feasible to be applied to MSME actors in Lamongan Regency.